The lending channel under optimal choice of monetary policy - Juha Kilponen; Alistair Milne (Bank of Finland, 2007)
Building on Cecchetti and Li (2005), we show that the bank lending channel affects monetary policy trade-offs only when interest rates affect marginal costs of production (ie when there is a cost channel of monetary policy) in the New Keynesian monetary policy model. In our calibrated model the resulting impact of the bank lending channel on output-inflation trade-offs is quantitatively small and of ambiguous sign. When bank capital varies counter cyclically and bank loan rates have a relatively large impact on marginal costs, variation of bank loan margins improves monetary policy trade-offs. The new Basel accord, by increasing capital requirements during economic downturns, offsets this beneficial impact.
URN:NBN:fi:bof-20140807423
Keywords: E51; E52; G21; 330; bank capital; bank lending; capital buffers; pro-cyclicality; capital regulation; cost channel; credit channel; loan margins; monetary trade-offs